PERAN KEPEMIMPINAN PARTISIPATIF DALAM MENINGKATKAN KOLABORATIF MASYARAKAT PADA PROGRAM “SUMBAR BERSATU” UNTUK PENGELOLAAN SAMPAH DI SUMATERA BARAT - Fahrezi, Iqbal; Syamsir, Syamsir; Dwi Berliana, Riffa; Sabrila, Filzah; Oktaviani, Elsa; Husna, Huriyatul; Febria Esa Rahman, Giva (Institute Agama Islam Tafaqquh Fiddin Dumai, 2025)
This research was motivated by the large amount of waste in West Sumatra, which was then developed by the United West Sumatra program in managing waste. The purpose of this study is to analyze the role of participatory leadership in increasing community collaboration in the